Analysis of the Impact of the New Two-Lane Shield Tunnel Underpass on the Existing Tunnels - Jinkui Li; Xinxia Fang; Yu Yang (Applied Sciences, 2025)
To address the issue of vertical settlement in existing tunnels beneath newly constructed two-lane tunnels, and to mitigate further impacts on tunnel operations, it is essential to investigate the effect of tunnel construction on the integrity of the existing tunnel structure. A calculation formula for the vertical displacement of the existing tunnel is derived by simplifying the calculation model and employing a two-stage analysis method. A three-dimensional numerical model of the double-line shield tunnel beneath the existing tunnel of Dalian Metro Line 4 is established using Midas GTS NX finite element software 2021(v1. 1). The study focuses on the influence of the new tunnel’s excavation on the existing tunnel, examining how various parameters in the shield construction process affect the settlement. Through comparative analysis of theoretical calculations, numerical simulations, and engineering monitoring data, the results indicate that the calculated displacement settlement trends align closely with the numerical simulation and are consistent with the field monitoring data. The findings provide valuable insights for the development of effective protection measures for existing tunnels during shield tunnel construction.